The Effectiveness of Local Culture-based Teaching Materials for Reading Comprehension Assisted by Adobe Flash CS6 for Fifth Grade Students in Elementary School - Intang, Hana; Sulfasyah; Idawati (Indonesian Values and Character Education Journal, 2023)
Teaching materials teachers use for fifth-grade students still need to take advantage of the environment around students. The textbooks used in learning still found examples from outside the student's environment. The examples given are outside the area where students live, so students need to gain initial knowledge of the material being studied. This study aims to analyze the effectiveness of local culture-based reading comprehension teaching materials as teaching materials for fifth-grade elementary school students. This type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research were fifth-grade elementary school students—questionnaire data collection techniques for teacher and student responses, and learning achievement tests. The results of this study indicate that teaching materials for reading comprehension based on local culture get a positive response. It is evidenced by the effectiveness of teaching materials obtained from increasing student learning outcomes obtained by the effectiveness of 0.76% with high criteria. Based on the research results, it can be concluded that this teaching material meets the criteria and is effective and appropriate for use as Indonesian language teaching material. This research can have positive implications for students. It can make students interested in participating independently in the learning process to create superior human resources, increase students' understanding of reading, and be more active and focused in learning.